PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT DI KANTOR KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW - Erna Manoppo; Agus Supandi Soegoto; Jumie S L. Mokoginta; Sicilya C. Mokoginta; Riskayanti Mappasompe (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The quality of public services is seen as one of the components that need to be realized by the company, because it has the influence to bring in new customers and can reduce the possibility of old customers to switch to other companies. Work discipline is defined when employees always come and go home on time, do all work well, comply with all company regulations and prevailing social norms. Customer satisfaction is a condition in which customer needs, wants, and expectations can be fulfilled through the products consumed. The purpose of this study was to determine the quality of public services and work discipline of employees on community satisfaction at the Lolak district office, Kab. Bolaang Mongondow. This research is a type of associative research with a survey approach. The analysis method used is multiple regression and hypothesis testing. Service quality and employee work discipline together affect community satisfaction at the Lolak sub-district office.